The Impact of Marketing Mix on the Number of Visits to Pediatric Dentists in Banjarmasin during the Covid 19 Pandemic - Ika Kusuma Wardani; Erika Norfitriah; Amalda Ayu Utami Hasibuan; Nadia Febrila Putri; Renie Kumala Dewi (Budapest International Research and Critics University, 2021)
The high number of dental problems in children hurts children's health. Pediatric dentists were deemed necessary to improve marketing strategies which were expected to attract visits to pediatric dentists. This study aims to analyze the impact of the marketing mix on the number of visits to pediatric dentists in Banjarmasin City during the covid 19 pandemic. This study used a cross-sectional quantitative method. The sampling technique used purposive sampling. Data were taken using a questionnaire that previously has been tested for validity and reliability. Data were analyzed using a multiple linear regression test. Product, promotion, and people partially have no significant impact on the number of visits to the pediatric dentist in Banjarmasin City during the covid 19 pandemics. Marketing mix has a simultaneous impact on the number of visits.